Co2+/3+/4+‐Regulated Electron State of Mn‐O for Superb Aqueous Zinc‐Manganese Oxide Batteries. Issue 6 (31st December 2020) - Ji, Jie; Wan, Houzhao; Zhang, Bao; Wang, Cong; Gan, Yi; Tan, Qiuyang; Wang, Nengze; Yao, Jia; Zheng, Zhaohan; Liang, Pei; Zhang, Jun; Wang, Hanbin; et al.
Abstract: Aqueous rechargeable Zn– MnO x batteries are very attractive due to their low‐cost and high energy density. However, Mn(III) disproportionation and Jahn–Teller distortion can induce Mn(II) dissolution and irreversible phase changes, greatly deteriorating the cycling life. Herein, a multi‐valence cobalt‐doped Mn3 O4 (Co‐Mn3 O4 ) with high capacity and reversibility, which lies in the multiple roles of the various states of doped cobalt, is reported. The Co 2+ doping between the phase change product δ‐MnO2 layer acts as a "structural pillar, " and the Co 4+ in the layer can increase the conductivity of Mn 4+ and hold the high specific capacity. More importantly, Co ion (Co 2+, Co 3+ ) doping can effectively inhibit the Jahn–Teller effect in discharge products and promote ion diffusion. Using X‐ray absorption spectra results and density functional theory modelling, the multiple roles of doped cobalt are verified. Specifically, the Co‐Mn3 O4 cathode shows high specific capacity of 362 mAh g –1 and energy density of 463.1 Wh kg –1 at 100 mA g –1 . After 1100 cycles at 2.0 A g –1, the capacity retention rate reaches 80%. This work brings a new idea and approach to the design of highly reversible Mn‐based oxides cathode materials for Zn‐ion batteries. Abstract : A multivalent cobalt (Co 2+, Co 3+ )‐doped Mn3 O4 nanosheet is successfully constructed on carbon nanosheet arrays (Co‐Mn3 O4 /CNA) as a cathode material for aqueous zinc‐ion batteries. Cobalt ions with different valence states play important roles in the first charging phase change product and discharge products, thereby improving the electrochemical performance of the battery.